A Gate Multiplexing Architecture‐Based Artificial Visual Sensor and Memory System. (21st December 2022) - Liao, Cen; Wang, Wei; Sun, Yi; Wang, Yongzhou; Liu, Sen; Tong, Peiwen; Li, Qingjiang
Abstract : The human visual system plays the most important role in information perception. Inspired by its structure and processing mechanism, novel optoelectronic memristor‐based artificial visual systems have emerged, thanks to the advantages of time latency and energy efficiency. However, the established systems lack a complete hardware supporting system to demonstrate the potential of large‐scale integration. Herein for the first time, a gate multiplexing architecture for optical signal sensor and memory integration is proposed, which can achieve multivalue storage of 3‐bit optical signal in the analog domain. Based on this novel structure, an artificial visual sensor and memory system (AVSMS) is implemented with a 5 × 6 photodiode array, an I / V conversion circuit, and a 32 × 32 1T1R memristor array for image sensor and memory integration. Furthermore, a parallel pipeline storage strategy is proposed to enable AVSMS to store 32 images with a size of 5 × 6 pixels and 3‐bit grayscale without erasing operation and achieve an ideal frame rate of more than 60 000 frames per second for high‐speed storage. Experimental results demonstrate that AVSMS can directly eliminate repeated background information in sequential images through peripheral hardware circuitry. The AVSMS provides a promising hardware solution for large‐scale image sensor and memory integration in artificial visual systems. Abstract : To achieve the integration of image sensor and memory, an artificial visual sensor and memory system (AVSMS) based on the 1T1R memristor array is proposed, which provides a promising hardware solution for large‐scale image sensor and memory integration in artificial visual systems.